Exercise tolerance can be enhanced through a change in work rate within the severe intensity domain: work above critical power is not constant - Dekerle, Jeanne; Souza, Kristopher Mendes de; Lucas, Ricardo Dantas de; Guglielmo, Luiz Guilherme Antonacci; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP] (Public Library Science, 2015)
The characterization of the hyperbolic power-time (P-tlim) relationship using a two-parameter model implies that exercise tolerance above the asymptote (Critical Power; CP), i.e. within the severe intensity domain, is determined by the curvature (W') of the relationship. The purposes of this study were (1) to test whether the amount of work above CP (W>CP) remains constant for varied work rate experiments of high volatility change and (2) to ascertain whether W' determines exercise tolerance within the severe intensity domain. Following estimation of CP (208 ± 19 W) and W' (21.4 ± 4.2 kJ), 14 male participants (age: 26 ± 3; peak [Formula: see text]: 3708 ± 389 ml.min-1) performed two experimental trials where the work rate was initially set to exhaust 70% of W' in 3 ('THREE') or 10 minutes ('TEN') before being subsequently dropped to CP plus 10 W. W>CP for TEN (104 ± 22% W') and W' were not significantly different (P>0.05) but lower than W>CP for THREE (119 ± 17% W', P<0.05). For both THREE (r = 0.71, P<0.01) and TEN (r = 0.64, P<0.01), a significant bivariate correlation was found between W' and tlim. W>CP and tlim can be greater than predicted by the P-tlim relationship when a decrement in the work rate of high-volatility is applied. Exercise tolerance can be enhanced through a change in work rate within the severe intensity domain. W>CP is not constant.